Avaliação de desastres no Rio Grande do Sul associados a Complexos Convectivos de Mesoescala / Evaluation of Hazards in Rio Grande do Sul, Brazil, Associated with Mesoscale Convective Complexes - Denilson Ribeiro Viana; Francisco Eliseu Aquino; Viviana Aguilar Muñoz (Sociedade & Natureza)
Mesoscale Convective Complexes (CCM) are organized clusters of convective clouds, which oftenarrive at Southern Region of Brazil and produce a variety of hazards. This study evaluated hazards associated with CCM events in the Rio Grande do Sul (RS) State, the southernmost of Brazil, betweenOctober and December of 2003. The detection of CCM was done using ForTraCC application –DSA/INPE. Data coming from Defesa Civil do RS (DCRS), the RS civil defense organization, andfrom the archives of Jornal Correio do Povo, a local newspaper, served as source material to evaluatethe hazards on the CCM event occurring days. During the period, 22 CCM events were identifiedover the RS. Based on DCRS reports, 90 incidents were associated with CCM events: strong galesand storms (42), flash floods (21), stream overflows (14), hail and strong gales (5), hail storms (3),swamping (2), floods (2) and earth flows (1). These CCM events caused the death of eleven people,of which six were in RS and the five in San Tomé, on the Argentinean side of the boarder. More than16,500 people were affected by hazards caused by CCM in the RS. Approximately 60% of the municipaldistricts affected requested emergency situation. On average, three to four events producesome type of hazard.